2018
DOI: 10.1111/ctr.13345
|View full text |Cite
|
Sign up to set email alerts
|

Canakinumab treatment in kidney transplant recipients with AA amyloidosis due to familial Mediterranean fever

Abstract: Canakinumab can be considered as a safe and efficient drug in preventing the FMF attacks in kidney transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
2
19
0
1
Order By: Relevance
“…While seven renal transplant patients were offered anakinra and the other immunosuppressive, no severe infections or drug interactions were seen. The previous studies that were carried out with renal transplant patients showed no severe adverse effect or drug interactions [19]. Multiple sclerosis is a possible adverse effect of any biological medication, and it was observed in one patient in this study.…”
Section: Discussionsupporting
confidence: 49%
“…While seven renal transplant patients were offered anakinra and the other immunosuppressive, no severe infections or drug interactions were seen. The previous studies that were carried out with renal transplant patients showed no severe adverse effect or drug interactions [19]. Multiple sclerosis is a possible adverse effect of any biological medication, and it was observed in one patient in this study.…”
Section: Discussionsupporting
confidence: 49%
“…The two patients who did not fulfil Tel-Hashomer criteria were both heterozygote for a disease-causing mutation. 25,28 Complete response to Canakinumab could not be achieved in either case.…”
Section: Efficacy Of Canakinumabmentioning
confidence: 97%
“…The most common dose of Canakinumab was 2mg/kg in patients <40kg, or 150mg in those above. 13,17,18,[20][21][22][23][24][25][26][27][28] In case of inadequate disease control, an increase in dose to 3-4mg/kg in those below 40kg or 300mg in those over was used in 8 studies. 10,14,15,19,23,[29][30][31] In 8 studies, 10,19,22,[25][26][27][28]31 Canakinumab was given at 4-weekly intervals, in 3 studies 18,21,24 it was given at 8-weekly intervals, whereas the remaining studies had dosing frequencies tailored to clinical needs and/or protocols, with the medication being given every 4, 6 or 8 weeks.…”
Section: Dosing Of Canakinumabmentioning
confidence: 99%
See 2 more Smart Citations